Model-based opti mization of phosphorus management strategies in Sur WWTP, Madrid. (15th April 2019) - Lizarralde, I.; Fernández-Arévalo, T.; Manas, A.; Ayesa, E.; Grau, P.
Abstract: Phosphorus has been considered as a pollutant to be removed from the wastewater. In the last years, however, it has been considered a valuable asset that needs to be recovered due to its shortage in nature. The study of optimum phosphorus management in wastewater treatment plants is not straightforward, due to the complexity of technologies and configurations that may be applied for phosphorus removal and recovery. In this context, plant-wide mathematical modelling and simulation tools are very useful for carrying out these studies. This paper introduces a study carried out at the Sur WWTP (Madrid) to assess optimum phosphorus management strategies based on the PWM. The mathematical model made it possible to describe the phosphorus flux and its characterization throughout the plant. Finally, an exploration by simulation with WEST™ was carried out to analyse different plant configurations and different operational strategies to optimize phosphorus management strategies in the Sur WWTP. Graphical abstract: Image 1 Highlights: Phosphorus recovery in WWTP. Validation of PWM for optimization of phosphorus management strategies. Phosphorus mapping and characterization through a WWTP. Application of PWM for full-scale case studies.